Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content1. The moderator role of Customer Characteristics in the relationship between E-marketing and the Mental Image of Sudanese Bank Customers in 2022Dr. Sana Gad Alla Elsheikh Eltahir, Mr. Abd Allah Muhammad Ali Idris, Mr. Sultan Muhammad Ahmed, Mr. Muhammad Ahmed Mahmoud2. Internal marketing management and its relationship to attracting administrative competencies  in local banks in the State of KuwaitMrs. Safia Mukhtar Ashkanani, Mrs. Aisha Meshaal Al-Mashaan3. Contributions of technological methods in improving the performance of employees in the Palestinian public sector by application to the Ministry of Social Development - Jenin DirectorateDr. Khaireya Radwan Yahya, Dr. Bahaa Ahmmad Yahia4. The Role of Zakat Chamber in Reducing Poverty in Sudan within the period 2018- 2020  - A Case Study of South Dar fur StateCo-Prof. Hassan Ali Osman Fatur5. The Impact of Foreign Direct Investment on the Growth of the Industrial Sector in the Kingdom of Saudi Arabia during the period (2000-2020)Dr. Lamia Shesha, Dr. Vivian Nasurldeen, Mrs. Nora Alhuthali6. Legal frameworks entrepreneurship projects in Saudi ArabiaDr. Enas Mohammed Ebrahim Elshite, Dr. Roweda Musa Abdel-Aziz Mohamed, Dr. Rasheeda Mahmoud Said Ahamed, Dr. Nagwa Wafaa Mohammed Sleem7. Historical cost vs. Fair value and their influence on earnings' qualityDr. Zakia Seid Benzerrouk, Dr. Khaldah Abdalla Mohammed Esawi, Dr. Lamia S. Shehab
Keywords: Journal of Economic, Administrative and Legal Sciences